Environmental Ecology Learning Based on Geographic Information Systems in Wonogiri Regency - Aziz Akbar Mukasyaf; Gilang Widi Ramadhan; Haris Risqianto (Universitas Muhammadiyah Surakarta, 2026)
Land ecosystem degradation in Wonogiri Regency, characterized by seasonal drought, land degradation, and land use change, requires management approaches based on ecological principles and geospatial technologies. However, the utilization of Geographic Information Systems (GIS) in geography education remains suboptimal, particularly at the teacher level. Therefore, this community service activity aimed to enhance the capacity of geography teachers in the MGMP (Subject Teacher Forum) of Wonogiri Regency in understanding regional ecology and integrating GIS into geography learning. The method employed was participatory training based on a service learning approach through workshops, with evaluation conducted using pre-test, post-test, and questionnaires. The activity involved 21 geography teachers. The results showed that the average pre-test score of 9.81 increased to 10.00 in the post-test, representing a 1.94% improvement with an N-gain value of 0.037 (low category). The paired sample t-test indicated that the improvement was not statistically significant (p > 0.05). Nevertheless, questionnaire results revealed positive responses from participants, with the majority reporting increased understanding, ease of material comprehension, and readiness to implement GIS in teaching. This indicates that the workshop was more effective in enhancing affective aspects and implementation readiness rather than short-term cognitive improvement. In conclusion, this activity serves as an initial stage in developing geospatial-based teacher capacity. Further intensive and sustainable programs are required to achieve more significant improvements in learning effectiveness.